Control of allergic rhinitis in four latin american countries: Rinola study - Silva, Diana L; de Barayazarra, Susana; Valero, Antonio; Garcia, Elizabeth; Uriarte, Silvia; Peñaranda, Augusto; Chapman, Edgardo; Garcia, Maria B; Ocampo, Jaime; Valencia, Viviana; Moreno, Sergio; Corelli, Silvana; et al. (Frontiers in Allergy, 2022)
Background Allergic rhinitis (AR) affects up to 40% of the general population, there are large-scale multicenter studies that have described its characteristics and few studies have focused on studying patients with AR in Latin America (LA). Methodology A cross-sectional, descriptive, multicenter study was carried out in four LA countries (Colombia, Argentina, Cuba and Peru). Patients diagnosed with AR between November 2017 and June 2020 were included. Sociodemographic and clinical data, sensitization profile and current treatment were collected in the Electronic Data Collection (BDClinic). Patients also filled out this questionnaires: Rhinitis Control Assessment Test (RCAT), Reflexive Total Nasal Symptom Score (rTNSS), Modified ARIA Criteria for AR Severity (mARIA) and ESPRINT-15. Risk of bias was examined by applying the STROBE checklist. Results The study included 412 patients. Median age was 25 years (15–39). Two hundred and twenty four (54.3%) were women. Nasal obstruction was present in 303 (73.5%). Three hundred and thirty four (81%) had a persistent AR. One hundred and twenty one (31.3%) had associated asthma. The most frequently positive skin tests were: Dermatophagoides pteronyssinus in 365 (88.6%) and Dermatophagoides farinae in 331 (81.3%). Four hundred and eleven patients (99%) reported that AR affected their quality of life. The median score of ESPRINT-15 was 1.87 (0.93–2.93), The mean values of RCAT and rTNSS were 19.01 (±4.59) and 5.4 (±2.97) respectively. Two hundred and fifty (60%) were receiving only oral antihistamines. Physicians decided to start nasal corticosteroids in 296 (71.8%). Only seventy patients (16.9%) were receiving immunotherapy. Conclusion These findings confirm that most of patients with AR in LA have a persistent disease with a negative impact on quality of life. Dust mites are the main sensitizers. These findings will allow to know the true impact of AR and can lead to a better disease management.